Bioderived fumaric acid for sustainable production of key active pharmaceutical ingredients: Dimethyl fumarate and Monomethyl fumarate. (September 2022) - Sebastian, Joseph; Osorio-Gonzalez, Carlos; Rouissi, Tarek; Hegde, Krishnamoorthy; Brar, Satinder Kaur
Abstract: Fumaric acid esters (FAEs) such as monomethyl fumarate (MMF) and dimethyl fumarate (DMF) are active pharmaceutical ingredients (API) used in the treatment of psoriasis and multiple sclerosis. The present work investigates the use of biobased fumaric acid obtained via submerged fermentation under fixed conditions for the production of FAEs. The effect of time, temperature, and sulphuric acid as a catalyzer on the conversion of fumaric acid to FAEs was elucidated. The optimal conditions for DMF synthesis were identified, using response surface methodology, to be 111 min incubation using 9.7% (v/v) sulphuric acid concentration at 98 °C. The use of biobased fumaric acid allows the use of renewable resources as the primary feedstock for the synthesis of FAEs in place of depleting petroleum resources. This value addition can have a positive impact on the techno-economic feasibility of a process towards bioproduction of fumaric acid, as well as contribute to rendering the synthesis of an API sustainable. Graphical Abstract: ga1 Highlights: Biobased active pharmaceutical ingredient synthesis. One pot conversion of fumaric acid to fumarate esters. Identification of optimal conditions for fumarate ester synthesis. 99.2% conversion of biobased fumaric acid to methyl esters achieved. FT-IR spectrum showed high similarity.